Pengelolaan Supervisi Klinis Di Sdn 3 Tegalrejo Kecamatan Wirosari Kabupaten Grobogan - MUKRIM, ABDUL, Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
ABSTRACT Abdul Mukrim. Q.100140063. Management of Clinical Supervision in SDN 3 Tegalrejo Wirosari Subdistrict Grobogan. Thesis. Graduate Muhammadiyah University of Surakarta. 2015. Teacher has the tasks of administration, management, development, monitoring, and technical services to support the educational process. Place of research at SDN 3 Tegalrejo Wirosari Subdistrict Grobogan. The purpose of this research 1. To describe the preparation of clinical supervision. 2. To describe the implementation of the results of clinical supervision. 3. To describe the results of clinical supervision. Data collection techniques using observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data using triangulation sources. Supervision techniques used are classroom visits. The activities observed during the process of supervision of the teachers' skills in teaching. Research result. 1. Skills teachers in learning to be better, 2. An increase in teacher skills. 3. The use of props is getting better, 4. Learning becomes more alive. 5. The results of student learning has increased in the achievement of KKM than before held supervision. The things that support and hinder the implementation of clinical supervision is. Which supports 1. Teachers become motivated to improve the quality of teaching and learning activities currently underway, 2. students become more active and interact while learning takes place. That hinder the implementation of supervision 1. sometimes collide with other activities, 2. With older teachers resulted cheekily. The follow up of clinical supervision is the principal always tries to guide teachers, to provide guidance to teachers in order to improve student learning outcomes. Principal also provides training carried out in accordance with the schedule of school activities. Keywords: clinical supervision, teacher, learning.